Factors Affecting Public Trust in Willing to Have A Covid 19 Vaccine - Purnama, Ria; Novriana, Nana; Listina, Febria (Journal of Language and Health, 2021)
From the Lampung Provincial Health Office as of April 13, 2021, for confirmed cases of Covid 19, which are 14,657 people and for the number of deaths, 795 people. This vaccination solution, of course, has again caused a polemic for some people. First, because of doubts about vaccine development, which was carried out with a fairly fast period of time, which was only about 1 year. The purpose of this study was to determine the factors that influence public confidence in being willing to vaccinate against COVID-19 for residents of RT 06 Jagabaya 2 Bandar Lampung Village in 2021. The research method used is descriptive quantitative research with a case control approach. The research was carried out on July 14, 2021 until July 30, 2021, at the research location, namely at RT 06 Jagabaya 2 Village, Way Halim District, Bandar Lampung City. The population in this study were all residents of RT 06 Jagabaya 2 Village with a vulnerable age of less than 18 years to the age of 58 years, which amounted to approximately 470 people. In this study the samples were grouped into 2, namely the case group (41 respondents) and the control group (41 respondents). The analysis in this study was carried out univariate and bivariate. The results showed that there is a relationship between knowledge, values, attitudes and beliefs with behavior, namely the availability of a Covid 19 vaccine in residents of RT 06 Jagabaya 2 Bandar Lampung Village in 2021. Health workers at the research location are expected to increase good knowledge about vaccines and provide an understanding that vaccines does not conflict with certain values, and the vaccine to be given is halal. And can also provide education about the importance of vaccines during a pandemic